Leveraging Cash Mobile-Based Application To Improve The Quality Of Mosque Financial Management System - Putri Aggraeni; Eka Sabrina Mustakim; Raodatul Fadilah; Kurnia Prima Putra (Journal of Embedded Systems, Security and Intelligent Systems, 2023)
In the era of technological advancement, the need for ease in data processing has become crucial. Recording mosque funds is one area that requires accurate and reliable information, considering the various types of cash transactions managed by the mosque, such as zakat, sadaqah, infak, wakaf, and others. However, the majority of mosque financial managers still rely on manual methods for recording and calculating finances, using books as reporting tools. This method carries high risks of data and report loss, as well as inefficiency in terms of speed and transparency. Therefore, the "MyCash Masjid" application was developed as a solution to enhance the quality of mosque financial management systems. MyCash Masjid is an application that encompasses income data, expenditure data, data summaries, and comprehensive reports. The use of information technology in the form of this application is expected to provide an effective solution in managing and recording mosque finances, as well as facilitating financial reporting for mosque administrators.